Ferrovia e mobilidade intrametropolitana: um estudo sobre o movimento pendular no cotidiano dos trabalhadores do ABC paulista - Silva, Neide Honorato da (2016)
This study aimed to evaluate the pendulum movement of ABC workers toward employers centers as an essential aspect of the reproduction of labor power in its broad inclusion in numerous tertiary in the metropolis of São Paulo. Seeks to characterize the intrametropolitan mobility and the problems of urban transport, focusing on metropolitan trains, identifying the diversity of its members and their difficulties on the way home to work. This study provides an understanding of the socio-spatial segregation process, evidenced in the long distances that separate the place of residence and place of work of the residents of the suburbs of Greater São Paulo. The implementation of the rail system in São Paulo had intimate relationships with coffee and favored the formation process of the metropolis. The São Paulo Railway was the first railway in the state of São Paulo, built in order to facilitate the transportation of coffee to the port of Santos. After going through several changes during the transition from the nineteenth to the twentieth century, today this railway is managed by CPTM (São Paulo Metropolitan Train Company), especially as part of the mobility and transport workers. Based on theoretical and methodological support consistent with the complexity of the subject, secondary data collection and statistical and field research, we believe present reflections indicative of the need for public policies that prioritize public transport